Correlation of GGT with AFP and diagnostic value of GGT for hepatocellular carcinoma - GAO Chun (Linchuang Gandanbing Zazhi, 2014)
ObjectiveTo analyze the correlation of gamma-glutamyl transpeptidase (GGT) level with alpha-fetoprotein (AFP) level and to re-evaluate the diagnostic value of GGT for hepatocellular carcinoma (HCC). MethodsFour hundred and seventy-two patients with HCC or liver cirrhosis, who were hospitalized in China-Japan Friendship Hospital from January 2003 to June 2009, were included in the study. The correlation between GGT and AFP was analyzed by Spearman nonparametric test. The cut-off values for the two parameters were determined based on their receiver operating characteristics (ROC) curves, areas under the ROC curve (AUCs), sensitivity, and specificity, and the diagnostic values were presented using their sensitivity, specificity, and correct index. Statistical analysis was performed using SPSS 17.0. Normally distributed continuous data were analyzed by independent-samples t test, while non-normally distributed continuous data were analyzed by Mann-Whitney U test. Categorical data were analyzed by Pearson chi-square test, continuity-corrected chi-square test, or Fisher’s exact test. ResultsAmong 472 patients, 224 were diagnosed with HCC, and 248 with liver cirrhosis. Compared with cirrhotic patients, HCC patients had a significantly higher GGT level (113 (58-254) U/L vs 38 (22-72) U/L, Z=-11.037, P＜0.001) and a significantly higher AFP level (429.5 (15.7-1210.0) ng/ml vs 5.7 (3.4-18.2) ng/ml, Z=-10.157, P＜0.001). A significant correlation was found between GGT and AFP (r=0.449, P＜0.001). The AUC was 0.784 for GGT and 0.788 for AFP. The cut-off value was 60 U/L for GGT and 20 ng/ml for AFP. The sensitivity was 74.1% for GGT, 71.8% for AFP, and 90.7% for a combination of the two parameters, the specificity was 70.2%, 77.6%, and 58.7%, respectively, and the correct index was 0.443, 0.494, and 0.494, respectively. ConclusionGGT may be regarded as one biomarker for HCC, and its level is significantly correlated with AFP level. The diagnostic value of AFP may not be improved when used in combination with GGT.